Understanding the mechanisms of methylammonium-induced thermal instability in mixed-FAMA perovskites - Tay, Darrell Jun Jie (2024)
Despite a recent shift toward methylammonium (MA)-free lead-halide perovskites for perovskite solar cells, high-efficiency formamidinium lead iodide (FAPbI3) devices still often require methylammonium chloride (MACl) as an additive, which evaporates away during the annealing process. In this article, it is shown that the residual MA+, however, triggers thermal instability. To investigate the possibility of an optimal concentration of MA+ that may improve thermal stability, the intrinsic thermal stability of pure FA, FA-rich, MA-rich, and pure MA perovskite films (FA1-xMAxPbI3, FAMA) is studied. The results show that the thermal stability of FAMA perovskites decreases with more MA+, under degradation conditions that isolate the intrinsic thermal stability of the material (i.e., without moisture and oxygen effects). X-ray diffraction (XRD), proton-transfer-reaction time-of-flight mass spectrometry (PTR-ToF-MS), photoluminescence (PL) and UV-visible spectroscopy, and depth-profiling X-ray Photoelectron Spectroscopy (XPS) are employed to show that the observed trend is mainly due to the decomposition of the MA+ cation, as opposed to other effects such as the precursor solvent and film morphologies. It is also found that the surfaces of these FAMA films are MA+ rich, although this phenomenon does not appear to affect thermal stability. Finally, it is demonstrated that this trend is unaffected by the presence of Spiro-OMeTAD atop the film, and thus solar cell devices should preserve this trend.